Integrating Vibe Coding and Artificial Intelligence into the Teaching Methods of Computer Science Teachers (Journal of Educational Sciences, 2026)
The rapid development of information technologies and artificial intelligence requires updating the content and methods of training to ensure the competitiveness of future specialists. One of the innovative approaches to teaching programming is Vibe Coding, which is based on the co-creation of software using intelligent agents. The user formulates tasks in natural language, and the neural network generates code, corrects errors and adds new functions. This approach accelerates the development process, makes it accessible and helps to unlock the creative potential of students and teachers. The purpose of the study is to analyze the possibilities of using Vibe Coding and AI tools in the teaching practice of computer science teachers. To achieve this goal, three main areas were considered: automation of practical tasks; personalization of learning and feedback for students; reducing the workload of teachers and increasing their creative potential. The experiment involved 120 students from the L. Gumilyov Eurasian National University. Ways to introduce visual elements of Vibe Coding and artificial intelligence. By automating routine tasks for identifying emotions using visual elements of artificial intelligence, teachers will have more time for methodological innovations, interdisciplinary connections and the development of students’ creative skills. The introduction of modern technologies into the learning process increases students’ digital literacy, accelerates the introduction of innovations, and stimulates the development of entrepreneurship and IT competencies.                                                               Keywords: higher education, future computer science teachers, innovative teaching technologies, artificial intelligence, vibe code application.